Penguatan Kapasitas Guru PAUD melalui Inovasi Alat Permainan Edukatif (APE) Berbasis Teknologi Informasi dalam Pembelajaran Interaktif - Amriani. H, Sri Rika; Amal, Azizah; Rusmayadi, Rusmayadi; Lismayani, Angri; Pratama, Muhammad Isbar (Program Studi Manajemen FEB UNM, 2026)
Early Childhood Education (PAUD) during the golden age requires optimal stimulation through Educational Game Tools (Alat Permainan Edukatif or APE). However, PAUD teachers in Bontomarannu District still face challenges such as low digital literacy and a dependence on static, conventional APE. This community service activity aims to strengthen the capacity of 30 PAUD teachers through training on Information Technology (IT)-based APE innovation to create more interactive learning. The method used was Participatory Action Research (PAR) with hands-on training and project-based learning approaches conducted over two days. The results showed a significant increase in the teachers' digital competence, where the average pre-test score of 46.2 increased to 81.6 in the post-test. Furthermore, participants successfully created various innovative IT-based APE products, such as digital educational cards and digital storybooks integrating local wisdom, with an average product quality score of 88.3, categorized as